Low shrinkage composite resins: influence on sealing ability in unfavorable C-factor cavities - Eliza Burlamaqui Klautau; Karina Kato Carneiro; Marcelo Figueiredo Lobato; Sissy Maria Mendes Machado; Mário Honorato Silva e Souza Junior (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The present investigation observed the sealing ability of low shrinkage composite resins in large and deep cavities, placed and photocured in one increment. Large, deep cavities (5.0 mm diameter and 2.5 mm deep) surrounded by enamel were prepared in bovine teeth, which were then divided into five groups. Groups 1, 2, 3 and 4: acid conditioning + Adper Single Bond (3M/ESPE, St Paul, MN, USA) and restoration with Aelite LS Posterior (BISCO Inc. Schaumburg, IL, USA) (G1); Filtek Z-350 (3M/ESPE,St Paul, MN, USA) (G2); Filtek Z-350 Flow (3M/ESPE, St Paul, MN, USA) (G3); Premisa (KERR Corporation, Orange, CA, USA) (G4). Group 5: Silorane Adhesive system (3M/ESPE, St Paul, MN, USA) + restoration with Filtek Low Shrinkage Posterior P90 (3M/ESPE, St Paul, MN, USA). After polymerization, the teeth were immersed in 0.5% basic fuchsine solution and immediately washed. Using the Imagetool Software, the extent of dye along the margins was calculated as a percentage of total perimeter. The restorations were then transversally sectioned and the depth of dye penetration was calculated in mm, using the same software. Kruskal-Wallis analysis for all groups showed no statistical differences for extent (p = 0.54) or depth (p = 0.8364) of dye penetration. According to this methodology, the so-called low shrinkage composite resins had the same sealing ability compared to regular and flowable nanocomposite materials.